Delta hepatitis: new approaches to therapy. (March 2016) - Soriano, Vincent; Labarga, Pablo; de Mendoza, Carmen; Fernández-Montero, José V; Treviño, Ana; Benítez-Gutiérrez, Laura; Peña, José M; Barreiro, Pablo
Hepatitis delta virus (HDV) infection is a neglected disease despite causing the most severe form of viral hepatitis. Over 15 million people are infected worldwide. IFN-α is largely inefficient and poorly tolerated. The discovery of sodium taurocholate cotransporting polypeptide as the cell receptor for HBV (and consequently for HDV) has allowed development of viral entry inhibitors (i.e., myrcludex-B). More recently, prenylation inhibitors (i.e., lonafarnib) that disrupt virion assembly are being tested. At this time, sustained suppression of HDV replication is the primary goal of hepatitis delta treatment, being associated with normalization of liver enzymes and histological improvement. The lack of persistent forms of HDV-RNA could provide unique opportunities for hepatitis delta cure using specific antivirals, even in the face of persistent HBV cccDNA.